2005
DOI: 10.1080/00015458.2005.11679721
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exogenous Melatonin on Experimental Colonic Anastomosis

Abstract: Results suggest that exogenous melatonin has no beneficial effect on the healing of colonic anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…[4] As OHP is the main determinant of collagen content within tissue, a correlation exists. [30] In the present study, higher levels of OHP were observed in the treatment group at all times, and significantly higher collagen deposits were also observed. BPs measured on the 7 th postoperative day were significantly higher in treated rats.…”
Section: Groupssupporting
confidence: 61%
See 1 more Smart Citation
“…[4] As OHP is the main determinant of collagen content within tissue, a correlation exists. [30] In the present study, higher levels of OHP were observed in the treatment group at all times, and significantly higher collagen deposits were also observed. BPs measured on the 7 th postoperative day were significantly higher in treated rats.…”
Section: Groupssupporting
confidence: 61%
“…[31] Similarly, Ozdogan et al found no beneficial effect of exogenous melatonin on colonic anastomosis. [30] On the other hand, Ozen et al reported that melatonin had a dose-independent positive effect on wound healing of colonic anastomosis in the presence of peritonitis. The authors found significantly higher burst pressure and glutathione levels in rats treated with a high dose of melatonin.…”
Section: Groupsmentioning
confidence: 99%
“…However, there are contradictory reports on melatonin in the literature. Some researchers believe that melatonin exerts a protective effect on wound healing, whereas others are completely opposed to the idea [8,10,25,26] . In light of our results, we share the same belief as other authors who support melatonin's positive effect on wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the question of appropriate dose and the formulation of melatonin, and the adjustment of circadian rhythms has not been resolved [9,10,26] . Previous studies showed that the dosage and the duration of exogenous melatonin administration is variable and depends on the purpose of usage.…”
Section: Discussionmentioning
confidence: 99%